Overlooking forensic evidence? A review of the 2014 International Protocol on the Documentation and Investigation of Sexual Violence in Conflict. Issue 1 (1st January 2017) - Maras, Marie-Helen; Miranda, Michelle D.
Abstract: The main task of this article is to determine whether the attention paid to the coverage of documenting, collecting and preserving physical and digital evidence is sufficient to ensure its admissibility in both national and international courts. This article undertakes this task by critically examining the 2014 International Protocol on the Documentation and Investigation of Sexual Violence in Conflict, which was part of the 2014 Global Summit to End Sexual Violence in Conflict. The objectives of this article are threefold. It first considers the special evidentiary rules of international courts. Secondly, it reviews the limited references to physical and digital evidence in the 2014 Protocol and discusses the potential pitfalls of failing to recognise the weight this evidence carries in national and international courts. Finally, the article recommends the use of trained forensic experts in the investigations of sexual violence and the establishment of uniform and comprehensive policies and procedures on the documentation, collection and preservation of forensic evidence, which are currently lacking in the 2014 Protocol.